Performance, metabolic, hemodynamic, and perceived exertion in the six-minute step test at different heights in a healthy population of different age groups - Oliveira,Túlio Medina Dutra de (2021)
Abstract Aim: This study aimed to compare the performance, metabolic, hemodynamic, and perceived exertion during the 6-minute step test (6MST) conducted with different step heights in healthy subjects and also to compare the performance between different age groups for each step height. The association between age, body mass index, level of physical activity, and lower limb measurements with performance were also evaluated. Methods: This is a cross-sectional study. Anthropometric measures, physical performance, and cardiovascular stress were evaluated during a self-paced 6MST with different step heights in healthy subjects in the age group of 18-59. All the participants underwent three-step tests (15 cm, 20 cm, and 30 cm) on the same day, in a randomized order. Results: Forty participants (20 men and 20 women) performed the tests. The performance in the test for the highest step was significantly lower compared to the step with the lowest height (152 ± 24 vs. 173 ± 27 and 184 ± 33; p < 0,05). The estimated peak oxygen consumption (VO2peak) increased by ∼2.5 mL.kg−1·min−1 with the increase in step height. Hemodynamic variables, such as percent of maximum heart rate (%HRmáx), and systolic blood pressure increased as the step height increased. There was a fair correlation between performance and the level of physical activity in the test with a step height of 15 cm and 20 cm. Conclusion: A higher step height caused greater cardiovascular stress, without exceeding the submaximal levels of the test, indicating that the 6MST can be used as an accurate instrument for evaluating aerobic capacity in healthy individuals.